Analisis Kemampuan Guru Pendidikan Agama Islam Terhadap Implementasi Kurikulum Merdeka SMKN 7 REJANG LEBONG - Sadam Husein; Destriani; Budi Lati (GHAITSA : Islamic Education Journal, 2025)
Education is an essential aspect of human life that contributes significantly to the transformation of individuals and society. As a basic right, education has a strategic role in improving the quality of life and accelerating national development. In an effort to transform developing countries into developed countries, education plays an important role in producing competent and adaptive human resources. One of the strategic steps in the world of education is the development of a curriculum that is relevant to the needs of the times. The change from the 2013 Curriculum to the Independent Curriculum is one of the important steps in dealing with the dynamics of these changes. The Independent Curriculum is designed to provide learning flexibility, encourage creativity, and adjust to the diverse individual potentials of students. This study uses a descriptive qualitative approach to gain a deep understanding of the phenomenon being studied. This study describes in detail the phenomenon of the implementation of the Independent Curriculum, both from an empirical point of view and the results of educational practice. The research subject includes literature studies from relevant scientific journals that have met academic standards, in order to provide an adequate theoretical foundation and empirical data. Data collection was carried out through literature review methods, interviews, observations, and documentation, with the aim of obtaining comprehensive information related to teachers' ability to implement the Independent Curriculum in PAI subjects. Through this approach, the research is expected to provide a comprehensive insight into the challenges faced by teachers and their ability to navigate curriculum changes. The results of this study are expected to be a reference for the improvement of educational practices in the future.